Pengaruh Gaya Kepemimpinan Terhadap Loyalitas Perangkat Desa Luksagu Kabupaten Banggai Kepulauan: The Impact of Leadership Style on Village Officials’ Loyalty in Luksagu, Banggai Islands Regency - Kamaru, Sri Mulyaningsih; Milang, Ichsan; Sadalia, Ramdan; Kansil, Rahmawati (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
This study aims to analyze the influence of leadership style on the loyalty of village officials in Luksagu Village, Tinangkung Utara Subdistrict, Banggai Kepulauan Regency. Employing a qualitative approach quantified into numerical data, the study involved 12 village officials as samples. Data were collected through questionnaires and analyzed using simple linear regression. The results indicated a positive and significant relationship between leadership style (X) and the loyalty of village officials (Y), with a correlation coefficient of 0.583 and a determination coefficient of 34%. This suggests that 34% of the loyalty of village officials is influenced by leadership style, while the remaining 66% is affected by other factors. The t-value of 2.269 exceeds the t-table value of 2.262, confirming the significant influence of leadership style on village officials' loyalty. The study highlights the critical role of leadership style in enhancing the loyalty of village officials to support effective village governance.